Produksi Biofuel Dari Limbah Cpo Dengan Katalis Berbasis Titanium Oksida Dan Implementasinya Pada Pembelajaran Kimia - Nurlia Latifah; Agus Sundaryono; Rina Elvia (University of Bengkulu, 2017)
Conversion of CPO waste into biofuel is one of the efforts to find alternative energy to overcome Indonesia's energy crisis. The resulting methyl ester was further processed into biofuel by cracking process with Ni/TiO2 and Co/TiO2 catalysts at temperature > 350oC for 2.5 hours followed by distillation. Educational research was done by doing the learning process by using biofuel module. The optimum biofuel yield was obtained from cracking methyl ester with 5% Ni/TiO2 catalyst and 3% Co/TiO2 catalyst respectively of 66,67 and 61,90%. The physical and chemical properties of cracked biofuels with Ni/TiO2 and Co/ TiO2 catalysts have complied with ASTM standards for biofuel except acid numbers. There is an increase in student learning outcomes before and after using the module.